B79 A national survey on the use of single-shot and continuous fascia iliaca comparatment block for the management of neck of femur fractures in the UK. (11th August 2022) - Mirza, M; Sachdeva, R; Mahmood, A
Abstract : Background and Aims: Hip fractures are extremely common and cause considerable pain which is associated with several negative patient outcomes. Perioperative analgesia may involve a fascia iliaca compartment block (FIB) which can be delivered as either a single-shot or via a continuous infusion of local anaesthetic. The aim of this survey was to investigate the practice of single shot or continuous FIB in management of neck of femur (NOF) patients within the UK. Methods: An anonymous survey was shared amongst trauma and orthopaedic consultants working at different hospitals in the National Health Service (NHS). Data was collected on a series of questions relating to the use of single shot and continuous FIB in the management of NOF fractures. Questions also pertained to the person responsible for delivering the block and whether ultrasound was used. Results: 34 consultants completed the survey. 100% of respondents stated their department use single-shot FIB and, when used, it was usually by members of the emergency department (ED) team (82%) and without ultrasound (82%). No respondents stated their department use continuous FIB in the ED for NOF fractures. Conclusions: Single-shot FIB appears to be widely used for the management of NOF fractures within ED, is usually delivered by members of the ED team and without ultrasound guidance. Continuous FIB appears to be used very rarely in the management for NOF fractures. This survey will lead onto a large prospective trial to further evaluate the potential of continuous FIB.